Lightning-induced voltage on distribution line due to inclined lightning channel - Rameli, Norhidayu (2013)
Cloud to ground discharge lightning is the most common type of lightning discharge to the ground. It contributes to at least 90 % of all negative charge discharges and demonstrates a higher value of peak current for the first stroke of the lightning. Thus,it may cause the failure of the shielding wire and also create an induced over-voltage on the power line. It is a fact that most of the distribution power lines are exposed to the possibility of disturbances and equipment damage caused by the effect of induced voltages. These induced voltages are influenced by various parameter conditions that result in either the induced voltage being tolerated or becoming an over-voltage on the power line. Lightning and power line parameters are recognized to influence the variation in value and condition of an induced voltage. In addition, most researchers have evaluated the induced voltage with respect to the lightning parameter by assuming the lightning channel is vertical. However, in reality, the lightning channel is not vertical. The lightning has an inclined angle when it strikes the surface of the ground which can be observed at a height of several hundred metres and this creates a variation value in the induced voltage on a power line. Thus, there is a need for specific research that addresses this induced voltage on distribution power lines due to the effect of an inclined lightning channel and protection on the line. The induced voltages in this study were calculated by implementing the procedure provided by IEEE 1410-2010. Also, the impedance of the line protection such as a line arrester was calculated by considering the guide line provided by IEEE Working Group 3.4.11 to mitigate the induced over-voltage on power lines. The results indicate that the induced voltage caused by the inclined and vertical lightning channels show a difference of at least 41%. Moreover, variations in the lightning parameters such as the inclined angle, the velocity of the return stroke and the striking distance from the lightning give a declining trend of induced voltage for an increase in the inclined angle. Furthermore, line parameters such as the height of the conductor line and observation point angle also give a declining trend of induced voltage for an increase in the observation point angle. The results of the induced voltage influenced by the various parameters revealed that at the smallest inclined angle of less than 30°, and at a very low speed of return stroke velocity, 1.2 × 108 m⁄s, at a minimum striking distance, 50m, at a 70°oobservation point angle and at the highest conductor line height, 15m, the lightning induced voltage exceeded the Basic Insulation Level (BIL) of 110kV and became an induced over-voltage. The line arrester results indicated that the induced over-voltage was suppressed to a safe level voltage of 33kV. Thus, the outcomes of these results may provide benefit for electrical power engineers when considering a protection scheme to take into account the variation value of induced voltage due to the variation of inclined angle. Also, it may provide an advantage for academic research to be able to accurately calculate the induced voltage due to a variation of the inclined angle in aninclined lightning channel.